Identification of platelet refractoriness in oncohematologic patients - Ferreira, Aline Aparecida (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVES: To identify the occurrence and the causes of platelet refractoriness in oncohematologic patients. INTRODUCTION: Platelet refractoriness (unsatisfactory post-transfusion platelet increment) is a severe problem that impairs the treatment of oncohematologic patients and is not routinely investigated in most Brazilian services. METHODS: Forty-four episodes of platelet concentrate transfusion were evaluated in 16 patients according to the following parameters: corrected count increment, clinical conditions and detection of anti-platelet antibodies by the platelet immunofluorescence test (PIFT) and panel reactive antibodies against human leukocyte antigen class I (PRA-HLA). RESULTS: Of the 16 patients evaluated (median age: 53 years), nine (56%) were women, seven of them with a history of pregnancy. An unsatisfactory increment was observed in 43% of the transfusion events, being more frequent in transfusions of random platelet concentrates (54%). Platelet refractoriness was confirmed in three patients (19%), who presented immunologic and non-immunologic causes. Alloantibodies were identified in eight patients (50%) by the PIFT and in three (19%) by the PRA-HLA. Among alloimmunized patients, nine (64%) had a history of transfusion, and three as a result of pregnancy (43%). Of the former, two were refractory (29%). No significant differences were observed, probably as a result of the small sample size. CONCLUSION: The high rate of unsatisfactory platelet increment, refractoriness and alloimmunization observed support the need to set up protocols for the investigation of this complication in all chronically transfused patients, a fundamental requirement for the guarantee of adequate management.